Tailoring morphology and mechanical properties of PLA/PBSA blends optimizing the twin-screw extrusion processing parameters aided by a 1D simulation software - Vito Gigante; Laura Aliotta; Bianca Dal Pont; Vincenzo Titone; Luigi Botta; Francesco Paolo La Mantia; Andrea Lazzeri (Polymer Testing, 2023)
To promote sustainability, the adoption of biobased and biodegradable plastics is a compelling solution. However, the successful utilization of these materials is contingent upon achieving desired properties and the ability to scale up production processes. Particularly in the case of blend systems, synergising the advantages of different polymers is essential. Moreover, assessing processing behavior and optimizing parameters are pivotal. This study aims to improve the extrusion process parameters selection using a 1D software-assisted Design of Experiments (DoE) approach. Polylactic acid (PLA) and polybutylene succinate-co-adipate (PBSA), varying PLA/PBSA ratios, were analysed simplifying and expediting the parameters selection. Remarkably, even in the absence of compatibility agents, this work demonstrates the potential to modify the structure, thereby influencing properties and performance by manipulating the process conditions.